Collaboration of Education Institution and Business World (Study at Activity of Event Marketing PT. Nasmoco Bengawan Motor Surakarta) - Yulius Slamet, Andri Astuti Itasari, Andre Rahmanto dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Education is a very basic and important in life. School and university are alwaysimprovement their education quality. It can be done by school or university with otheraspect. One of them from the aspects is a company. A company creates the cooperationwith school or university to take a part in education. PT. Nasmoco Bengawan Motor is oneof company which takes part in innovation education through event marketing. Thiscompany is working in automotive. A school or university can be cooperated with thiscompany if they want to make an event. This company is ready to make the event besuccessful. This study researches the cooperation between PT. Nasmoco Bengawan Motorand school or university to increase the quality in education. The research uses exploratoryqualitative method. Data are by depth interview technique, observation, and documentanalysis to get information. The research uses data validity and qualitative data analysis.The result shows that PT. Nasmoco Bengawan Motor did the cooperation with school oruniversity in Surakarta consistently, to increase the quality in education and indirectly thecompany plant a positioning in customers about the company. So, the company has aneffort to influence the customers.Keyword: PT. Nasmoco Bengawan Motor, event marketing, school cooperation program, innovationin education